Eligibility for differentiated models of HIV treatment service delivery: an estimate from Malawi and Zambia. (1st March 2020) - Hoffman, Risa M.; Balakasi, Kelvin; Bardon, Ashley R.; Siwale, Zumbe; Hubbard, Julie; Kakwesa, Gift; Haambokoma, Mwiza; Kalua, Thoko; Pisa, Pedro; Moyo, Crispin; Dovel, Kathryn; Xulu, Thembi; et al.
Abstract : Background: Little is known about the proportion of HIV-positive clients on antiretroviral therapy (ART) who meet stability criteria for differentiated service delivery (DSD) models. We report the proportion of ART clients meeting stability criteria as part of screening for a randomized trial of multimonth dispensing in Malawi and Zambia. Methods: For a DSD trial now underway, we screened HIV-positive clients aged at least 18 years presenting for HIV treatment in 30 adult ART clinics in Malawi and Zambia to determine eligibility for DSD. Stability was defined as on first-line ART (efavirenz/tenofovir/lamivudine) for at least 6 months, no ART side effects, no toxicity or infectious complications, no noncommunicable diseases being treated in ART clinic, no lapses in ART adherence in the prior 6 months (>30 days without taking ART), and if female, not pregnant or breastfeeding. Results: In total, 3465 adult ART clients were approached between 10 May 2017 and 30 April 2018 (Malawi: 1680; Zambia: 1785). Of the 2938 who answered screening questions (Malawi: 1527; Zambia: 1411), 2173 (73.5%) met criteria for DSD eligibility (Malawi: 72.8%; Zambia: 74.3%). The most common reasons for ineligibility were being on ART less than 6 months (9.6%) and a regimen other than standard first-line (7.9%). Conclusion: Approximately three-quarters of all adult clients presenting at ART clinics in Malawi and Zambia were eligible for DSD using a typical definition of stability. High uptake of DSD models by eligible clients would have a major impact on the infrastructure and the allocation of HIV treatment resources.